Case report: Abdominal mesothelioma in Atelerix albiventris - Troncoso, Ignacio; Brown, John; Isla, Carla; Lajara, Juan Manuel; Ebner, Max; Fehrmann-Cartes, Karen (Frontiers in Veterinary Science, 2024)
Hedgehogs, as exotic species, exhibit a heightened susceptibility to various neoplastic conditions affecting diverse bodily systems, particularly the tegumentary, hemolymphatic and digestive systems. Among these, epithelial tumors are the most prevalent, followed by round cell and mesenchymal tumors. A striking characteristic is the malignant nature of over 8% of these tumors, leading to a generally unfavorable prognosis. This study aims to present a unique case involving a 2.5-year-old male African pygmy hedgehog in Concepción, Biobío District, Chile, diagnosed with a mesenchymal neoplasia originating from mesothelial cells. The hedgehog presented to the veterinary clinic with acute abdominal pain, prompting ultrasound, comprehensive cytological, histopathological, and immunohistochemical analyses. Abdominal ultrasound, a mass was observed, while its cytology revealed the presence of malignant cells. The histopathological examination unveiled a diffuse mesothelial cell tissue interwoven with abundant fibrous tissue and small cysts containing serous fluid, all enveloped by flattened or cuboidal cells of mesothelial origin. Immunohistochemistry further confirmed the diagnosis, demonstrating positive immunostaining for calretinin and mesothelin markers, corroborating the diagnosis of fibrous malignant peritoneal mesothelioma. This case underscores the complexity of neoplastic conditions in hedgehogs and emphasizes the importance of multimodal diagnostic approaches for accurate identification and understanding of these rare diseases.